Diagnostic and prognostic value of systemic immune-inflammation index for heart failure: a systematic review and meta-analysis - Yu, Jiajun; Zuo, Tian; Peng, Sihan; Xu, Danping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIncreasing evidence has indicated the potential correlation between Systemic Immune-Inflammation Index (SII) and the incidence and prognosis of patients with heart failure (HF). However, the association remains unraveled in the existing research.MethodsA literature search was systematically conducted across PubMed, Embase, Web of Science, and the Cochrane Library from their respective inceptions to July 2024, aiming to identify studies investigating the association between SII and both the incidence and clinical outcomes of HF patients. The primary outcomes included incidence and mortality rates, which were assessed using risk ratios (RR) and corresponding 95% confidence intervals (CIs). To assess the robustness of the findings and to identify potential sources of heterogeneity, sensitivity analyses and subgroup analyses were conducted. Meta-analyses were carried out using Review Manager (v5.4) and STATA (v15.0).ResultsFifteen studies comprising 77,917 patients were included. The pooled data demonstrated no significant association between SII and the incidence of HF (RR = 1.22, 95%CI: 0.92–1.62; p = 0.16). However, a significant correlation was identified between elevated SII and increased mortality risk (RR = 1.44, 95%CI: 1.29–1.61; p < 0.00001). Furthermore, subgroup analyses revealed the association between SII and mortality in patients with HF was not influenced by sample size, age, country, study design, or ejection fraction. In contrast, the association between SII and incidence of HF was affected by country, while no significant effect was observed in the other subgroups.ConclusionAs a reliable biomarker, SII exhibits significant efficacy in prognostic evaluation for HF patients and provides valuable insights to inform clinical decision-making in the HF population.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, PROSPERO CRD42024582003.